(3EOGQI GdeTJQjGJ hGdeHjYGJ hGdeNGRfs - (3eMeO(B, (3GdUjQajs; (3HhLjQj MSf eMeO(B, s ((3GdHMQjf(B:s (3eDSSI dhQO GdYGdejI ddTDhf GdLGeYjI,s, 2006)
(3eGgjI GdTQGA hCgejJg, JfXje EOGQI GdehGQO, GdCUhd GdYdejI ddTQGA, eaghe GdeNRhf hCfhGYg, ELQGAGJ GdJNRjf, GdHjY GdTNUj(B. s
(3HjHdjhZQGajG(B: (3U(B.130s
Keywords: (3GdGOGQIs; (3GdeNRhfs